Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3389/fphys.2020.00055
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic and Functional Study of Intersex, a Gene Related to Female Fertility in Bemisia tabaci

Abstract: The intersex (ix) gene acts in concert with doublesex (dsx) at the end of the sex determination hierarchy to control somatic sexual differentiation in Drosophila melanogaster. Here, we report the Drosophila ix homolog in Bemisia tabaci (Btix) with differential splicing events. Four isoforms were found in B. tabaci adults, including two sex-specific transcripts (Btix F and Btix M). Knockdown of Btix had no measurable effects on female morphological phenotypes but reduced the expression of the vitellogenin gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Nevertheless, the Dmix is transcribed non-sex specifically and contains only one exon in D. melanogaster [ 1 ]. Despite discoveries of sex-specific splicing transcripts of ix in many insects, e.g., a testis-specific isoform of ix founded in B. mori [ 20 ], female pupae stage-specific ix isoform described in M. vitrata [ 3 ] and two sex-specific variants of ix reported in B. tabaci [ 5 ], the underlying functions of these sex-specific isoforms remain largely unknown. In BPH, the Nlix produces two isoforms by alternative splicing, both of which are expressed non-sex specifically.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the Dmix is transcribed non-sex specifically and contains only one exon in D. melanogaster [ 1 ]. Despite discoveries of sex-specific splicing transcripts of ix in many insects, e.g., a testis-specific isoform of ix founded in B. mori [ 20 ], female pupae stage-specific ix isoform described in M. vitrata [ 3 ] and two sex-specific variants of ix reported in B. tabaci [ 5 ], the underlying functions of these sex-specific isoforms remain largely unknown. In BPH, the Nlix produces two isoforms by alternative splicing, both of which are expressed non-sex specifically.…”
Section: Discussionmentioning
confidence: 99%
“…Intersex ( ix ) is a gene involved in the sex-determining cascade of insects. It was first well-characterized in Drosophila melanogaster [ 1 ] and showed apparently deep conservation in insect species, as Bombyx mori [ 2 ], Maruca vitrata [ 3 ], Cyclommatus metallifer [ 4 ], Bemisia tabaci [ 5 ] and Oncopeltus fasciatus [ 6 ]. In D. melanogaster , the DmIX protein forms a complex with the female-specific product of Dmdsx (DmDSX F ) at the bottom of the sex-determining cascade, thereby implementing the sex-specific differentiation of sexually dimorphic characters among female individuals [ 1 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraordinary experimental efforts have been conducted to elucidate the role of Nlix in biological processes of insects, such as growth and development, sex differentiation, and reproduction [ 29 , 30 , 31 , 32 ]. The function of Nlix in regulating microbial community composition was first discovered.…”
Section: Discussionmentioning
confidence: 99%
“…The intersex ( ix ) gene is well conserved in insects, nevertheless, it has a multiplicity of functions in different species. For instance, it participates in sex differentiation, regulates external genital development, and female fecundity [ 29 , 30 , 31 , 32 ]. In our previous studies, we found that knocking out Nlix in nymphs led to the arrest of reproductive system development and failure of molting in BPHs.…”
Section: Introductionmentioning
confidence: 99%